Innovative delivery systems for epicutaneous immunotherapy - Wang, Zhen; Wu, Lingzhi; Wang, Wei (Frontiers in Immunology, 2023)
Allergen-specific immunotherapy (AIT) describes the establishment of peripheral tolerance through repeated allergen exposure, which qualifies as the only curative treatment for allergic diseases.Although conventional subcutaneous immunotherapy (SCIT) and sublingual immunotherapy (SLIT) have been approved to treat respiratory allergies clinically, the progress made is far from satisfactory.Epicutaneous immunotherapy (EPIT) exploits the skin's immune properties to modulate immunological response, which is emerging as a promising alternative and has shown effectiveness in many preclinical and clinical studies for both respiratory and food allergies. It is worth noting that the stratum corneum (SC) barrier impedes the effective delivery of allergens, while disrupting the SC layer excessively often triggers unexpected Th2 immune responses. This work aims to comprehend the immunological mechanisms of EPIT, and summarize the innovative system for sufficient delivery of allergens as well as tolerogenic adjuvants. Finally, the safety, acceptability, and cost-effectiveness of these innovative delivery systems are discussed, which directs the development of future immunotherapies with all desirable characteristics.